The role of hepatic biopsy in liver graft evaluation during liver procurement - M. S. Novruzbekov; O. D. Olisov; V. A. Gulyaev; K. N. Lutsyk; E. I. Ryaboshtanova; A. S. Tertychnyy; O. F. Vostrikova; A. S. Rozhenkov (Трансплантология (Москва))
Abstract. Using a steatotic graft in liver transplantation (LT) can lead to a poor function and high mortality. The role of the rapid liver graft biopsy processing was studied. The liver grafts of potential donors were assessed for hepatic steatosis.Material and methods. The study included 341 cases of cadaveric donor liver transplantations. Patients were divided in two groups: the study group where the rapid graft biopsy processing was performed (n=163) and the comparison group (n=178) without biopsy processing. Livers with macrosteatosis of over 50% of graft parenchyma or with severe necrosis and structural damage were discarded.Results. The rates of ischemic reperfusion injury (IRI), initial poor graft function (IPGF), and primary graft nonfunction (PNF) were significantly lower in the study group. There were no significant differences between two groups in cold ischemia time.Conclusion: rapid histological examination provides a useful tool to avoid life threatening LT complications such as severe IRI, IPGF, and PNF.